Quiet Silencing the brain chatter and believing that you're good enough - Cotton, Fearne; Cotton, Fearne; Underwood, Jessica May (London Orion Spring, 2018)
This book is about taming the bad inner voice - the one that has the power to overthrow gut instinct and talk us out of new adventures. We are all brimming with inner wisdom, yet we allow negative thoughts to confuse us. We forget how capable and strong we can be. There is confidence there even if it's hidden; there is courage, beauty, wisdom and belief - we just need some quiet to notice it. Love, Fearne xxx - From Sunday Times bestselling author Fearne Cotton, this is the handbook for modern life we all need. Including expert advice, ideas to put into practice, adventures to complete and interviews with everyone from Bryony Gordon to Billie Piper, Quiet seeks out ways to help you tune out the negative backchat that holds you back, so you can hear the positives that will guide you forwards
Keywords: Psychology; Quiet